2012
DOI: 10.1603/an11078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Subterranean Termites of the GenusReticulitermes(Isoptera: Rhinotermitidae) from Korea

Abstract: Molecular and taxonomic studies of subterranean termites in the genus Reticulitermes (Isoptera: Rhinotermitidae) have suggested that Reticulitermes speratus kyushuensis Morimoto is the only species that occurs in Korea. However, the specimens studied to date were collected from a limited number of locations, and basic information about the distribution, taxonomy, and molecular characteristics of this genus in Korea is still lacking. In this study, we collected Reticulitermes specimens from 50 sampling sites di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
(20 reference statements)
2
9
0
Order By: Relevance
“…For instance, our results revealed that R. chinensis and R. leptomandibularis are closely related, which supports their previous classification as subspecies (Krishna et al, 2013). Our results also confirmed that the Japanese species, R. speratus, is composed of two main lineages that may be subspecies (Kim et al, 2012;Park et al, 2006). However, our study also highlights the need for fur ther research into the taxonomy and systematics of the genus Reticulitermes.…”
Section: Considerations On Taxonomy and Systematicssupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, our results revealed that R. chinensis and R. leptomandibularis are closely related, which supports their previous classification as subspecies (Krishna et al, 2013). Our results also confirmed that the Japanese species, R. speratus, is composed of two main lineages that may be subspecies (Kim et al, 2012;Park et al, 2006). However, our study also highlights the need for fur ther research into the taxonomy and systematics of the genus Reticulitermes.…”
Section: Considerations On Taxonomy and Systematicssupporting
confidence: 90%
“…The vast majority of contemporary species identified so far have been collected in western Europe, North America (in the USA), or in eastern Asia (mostly in Japan and China). Almost all phylogenetic and phylogeographic studies have dealt with taxa collected in one of these geographic regions and have focused on either European (Austin et al, 2007(Austin et al, , 2002Jenkins et al, 2001;Kutnik et al, 2004;Lefebvre et al, 2008;Leniaud et al, 2010;Luchetti et al, 2007Luchetti et al, , 2013aLuchetti et al, , 2004Marini and Mantovani, 2002;Uva et al, 2004;Velonà et al, 2010), North American (Austin et al, 2007;Copren et al, 2005;Ye et al, 2004), or Japanese taxa (Kim et al, 2012;Park et al, 2006). Only a few studies have investigated the phylogenetic relationships among European, North American and Asian taxa in targeted analyses (Austin et al, 2004(Austin et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Becker (1969) first reported this species from Korea based on morphology, but there have been questions about the number of termite species in Korea because of the lack of taxonomic studies (Park and Bae, 1997). In the last ten years, several reports using mitochondrial or nuclear gene sequences, have verified the prevalence of R. speratus kyushuensis (Park et al, 2006(Park et al, , 2013Kim et al, 2012). However, recently, Kim et al (2012) found another Reticulitermes sp.…”
Section: Introductionmentioning
confidence: 98%
“…In the last ten years, several reports using mitochondrial or nuclear gene sequences, have verified the prevalence of R. speratus kyushuensis (Park et al, 2006(Park et al, , 2013Kim et al, 2012). However, recently, Kim et al (2012) found another Reticulitermes sp. They identified as Reticulitermes kanmonensis Takematsu, 1999 based on a BLAST search (http://blast.ncbi.nlm.nih.gov/); however, due to the lack of morphological verification, it is still ambiguous whether R. kanmonensis is well distributed in Korea.…”
Section: Introductionmentioning
confidence: 98%
“…In the previous study, R. speratus kyushuensis displayed various morphological variations and showed 3 haplotypes (Lee et al 2015). In another study, R. speratus found in Korea showed 2 different haplotypes (Kim et al 2012). Both studies raised a possibility that subspecies of R. speratus other than R. speratus kyushuensis may be present in Korea.…”
Section: Introductionmentioning
confidence: 91%